1993
DOI: 10.1002/jcla.1860070112
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anti‐thyroglobulin IgG in urine of patients with autoimmune thyroid diseases by sensitive enzyme immunoassay (immune complex transfer enzyme immunoassay)

Abstract: Anti-thyroglobulin IgG in urine of patients with Graves' disease and chronic thyroiditis and healthy subjects was measured by a sensitive enzyme immunoassay (immune complex transfer enzyme immunoassay). Anti-thyroglobulin IgG in dialyzed urine was reacted simultaneously with 2,4-dinitrophenylated thyroglobulin and thyroglobulin-beta-D-galactosidase conjugate. The immune complex formed consisting of the three components was trapped onto polystyrene balls coated with (anti-2,4-dinitrophenyl group) IgG, eluted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…10,15,16 In contrast, IgG autoantibodies can be found in the urine of patients with autoimmune thyroid disease, 17,18 pernicious anaemia, 19 and interstitial cystitis. 20 In addition, there is ample evidence demonstrating that IgG-class HIV-1 antibodies can be detected in the urine of HIV-1 seropositive and even seronegative patients.…”
mentioning
confidence: 99%
“…10,15,16 In contrast, IgG autoantibodies can be found in the urine of patients with autoimmune thyroid disease, 17,18 pernicious anaemia, 19 and interstitial cystitis. 20 In addition, there is ample evidence demonstrating that IgG-class HIV-1 antibodies can be detected in the urine of HIV-1 seropositive and even seronegative patients.…”
mentioning
confidence: 99%
“…Those levels were well correlated to serum levels, whether the values were corrected by the concentration of creatinine or IgG in urine or IgG in both urine and serum (Fig. 25) (14). This indicated that antithyroglobulin IgCi in urine derived from that in blood.…”
Section: -D-galactosidase From E Coli As Label (Open Symbols) and mentioning
confidence: 73%
“…The presence of antithyroglobulin IgG at low concentrations in healthy subjects was confirmed by preincubation of sera with excess of thyroglobulin in the presence of excess of inactive P-D-galactosidase ( Fig. 15) (12,14).…”
Section: Application Of Immune Complex Transfer Enzyme Immunoassay Fomentioning
confidence: 85%
See 2 more Smart Citations